Exercise interventions to reduce anxiety in mid-life and late-life anxiety disorders and subthreshold anxiety disorder: a systematic review. (June 2022) - Chong, Terence W.H.; Kootar, Scherazad; Wilding, Helen; Berriman, Sarah; Curran, Eleanor; Cox, Kay L.; Bahar-Fuchs, Alex; Peters, Ruth; Anstey, Kaarin J.; Bryant, Christina; Lautenschlager, Nicola T.
Background: Anxiety disorders are highly prevalent and cause significant distress, disability, and cost. Medication adverse effects and interactions increase in mid-life and late-life, highlighting the need for effective non-pharmacological interventions. Objectives: We aimed to evaluate the extent of evidence supporting exercise interventions for anxiety and subthreshold anxiety disorders in mid-life and late-life. Design: Systematic review. Data Sources and Methods: We searched MEDLINE, PsycINFO, Embase, Emcare, Ovid Nursing, CINAHL Plus, Cochrane Library, Health Collection, Humanities & Social Sciences Collection, andhttps://clinicaltrials.gov databases for trials published January 1994–May 2019. Randomised controlled trials of exercise interventions involving aerobic exercise or resistance training for adults aged 40 years and above with anxiety or subthreshold anxiety disorders in residential or health settings were identified. The primary outcome was change in anxiety. We excluded trials including participants aged below 40 years, participants with diagnosis of separation anxiety, selective mutism, obsessive-compulsive disorder, acute stress disorder and post-traumatic stress disorder, and head-to-head comparisons of interventions. Trial quality was assessed using the Cochrane Risk of Bias Tool and evidence synthesised in narrative form. Results: Four trials totalling 132 participants met inclusion criteria, although some had methodological limitations. Interventions included a home-based resistance training intervention, supervised group-based aerobic intervention, Tai Chi intervention, and supervised group-based aerobic and strength intervention. Three trials included late-life participants and the fourth mid-life. Three trials demonstrated greater reductions in anxiety in the intervention group compared with control. The fourth trial showed pre–post reductions in anxiety in both groups, with between-group difference not reaching statistical significance. Conclusion: There is limited supportive evidence suggesting that exercise interventions have potential to be effective, feasible and safe non-pharmacological interventions for anxiety and subthreshold anxiety disorders in mid-life and late-life. The heterogeneity, limited number and high risk of bias of some trials meant that we were not able to conduct a meta-analysis. Tailoring of interventions may improve uptake and reduce dropout. The paucity of research in this area with only four included trials demonstrates the urgent need for future and larger trials to provide proof of concept, data about effective types and doses of exercise interventions, and guidance to community, clinical, and public health services.